A Subcarrier and Power Allocation Algorithm for OFDMA Full-Duplex Systems - Cirik, A.; Rikkinen, K.; Rong, Yue (IEEE, 2015)
In this paper, we focus on subcarrier and power allocation for an orthogonal frequency division multiple access (OFDMA) full-duplex (FD) system. A three-step algorithm is proposed to maximize the sum-rate of the system subject to individual rate constraints at the uplink and downlink users, and transmit power constraints at the base station (BS) and uplink users. The steps are: 1) Subcarrier allocation that considers user target rate requirements, 2) residual subcarrier allocation that further increases the sum rate, and 3) power allocation based on iterative water-filling (IWF). Simulation results reveal that the proposed FD scheduling improves the sum-rate over thetraditional half-duplex (HD) and round-robin (RR) scheduling significantly under the self-interference cancellation levels that has been recently achieved.